2018
DOI: 10.1007/s00405-018-5120-3
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and functional long-term results of endoscopic butterfly inlay myringoplasty

Abstract: We suggested that endoscopic butterfly inlay myringoplasty is a safe surgical method with high graft success and effective hearing reconstruction. Follow-up is necessary for at least 2 years for precise anatomical and functional evaluation of the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Darouassi et al [2] and Zhang et al [4] reported that the subtotal perforation was the most frequent representing --respectively --47% and 32.8%. Shoman [3] and Karabulut et al [5] highlighted that the anterior perforation was the most common, being respectively 40% and 35.7%, which goes in line with our study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Darouassi et al [2] and Zhang et al [4] reported that the subtotal perforation was the most frequent representing --respectively --47% and 32.8%. Shoman [3] and Karabulut et al [5] highlighted that the anterior perforation was the most common, being respectively 40% and 35.7%, which goes in line with our study.…”
Section: Discussionsupporting
confidence: 93%
“…However, the mean age of the patients --in our series --ranges from 16 to 54, with an average of 35 years. The gender distribution was variable in the literature, even though in the majority of the series, there was a female predominance [2][3][4][5]. Altuna et al [6] revealed some pathological backgrounds in 99 cases: 52 of them had already undergone a former surgery (49 cases of myringoplasty and three cases of grommet insertion).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful closure was achieved in 95.5% with statistically significant air-bone-gap improvement of 8.5 dB as an alternative minimally invasive surgical technique for small anterior perforations. Karabulut et al (2018) evaluated the long-term anatomical and functional results of endoscopic butterfly myringoplasty and reported a GIR of 98.2% after 1 year and 94.6% after 2 years 37 . Audiometric measurements revealed significantly improved hearing threshold and air-bone-gap at 6, 12 and 24 months compared to the preoperative results.…”
Section: Butterfly Myringoplastymentioning
confidence: 99%
“… 24. Karabulut et al showed that the mean preoperative ABG was 24.2 ± 3.8 dB, the mean ABG on the 12th postoperative month was 17.1 ± 3.5 dB, and the mean ABG on the 24th postoperative month was 12.4 ± 3.1 dB 25. .…”
mentioning
confidence: 99%